Application of step and beat alignment approaches and its effect on gait in progressive multiple sclerosis with severe cerebellar ataxia: A proof of concept case study. (March 2022) - Moumdjian, Lousin; Moens, Bart; Van Wijmeersh, Bart; Leman, Marc; Feys, Peter
Background: In a case report of a progressive multiple sclerosis with cerebellar impairments, we reported that synchronisation of steps to beats was possible only at −12% of usual walking cadence during 1 minute of walking. Objectives and methods: Here, we investigate the effect of synchronisation using two different alignment approaches on the patient's gait pattern over 2 minutes of walking, compared to walking in silence. Results and conclusion: This proof of concept showed that the adaptive approach was successful resulting in an improved gait pattern compared to the other conditions, providing preliminary evidence to support a full-scale intervention study.